Comparative study of environmental pollutants bisphenol A and bisphenol S on sexual differentiation of anteroventral periventricular nucleus and spermatogenesis - Naham John; Humaira Rehman; Suhail Razak; Mehwish David; Waheed Ullah; Tayyaba Afsar; Ali Almajwal; Iftikhar Alam; Sarwat Jahan (BMC, 2019)
Abstract Background Bisphenol A is well known endocrine-disrupting chemical while Bisphenol S was considered a safe alternative. The present study aims to examine the comparative effects of xenobiotic bisphenol-A (BPA) and its substitute bisphenol-S (BPS) on spermatogenesis and development of sexually dimorphic nucleus population of dopaminergic neurons in the anteroventral periventricular nucleus (AVPV) of the hypothalamus in male pups. Methods Sprague Dawley rat's pups were administered subcutaneously at the neonatal stage from postnatal day PND1 to PND 27. Thirty animals were divided into six experimental groups (6 animals/group). The first group served as control and was provided with normal olive oil. The four groups were treated with 2 μg/kg and 200 μg/kg of BPA and BPS, respectively. The sixth group was given with 50 μg/kg of estradiol dissolved in olive oil as a standard to find the development of dopaminergic tyrosine hydroxylase neurons in AVPV regions. Histological analysis for testicular tissues and immunohistochemistry for brain tissues was performed. Results The results revealed adverse histopathological changes in testis after administration of different doses of BPA and BPS. These degenerative changes were marked by highly significant (p < 0.001) decrease in tubular and luminal diameters of seminiferous tubule and epithelial height among bisphenols treated groups as compared to control. Furthermore, significantly increased (p < 0.001) TH-ir cell bodies in the AVPV region of the brain with 200 μg/kg dose of BPA and BPS was evident. Conclusion It is concluded that exposure of BPA and BPS during a critical developmental period can structural impairments in testes and affects sexual differentiation of a dimorphic dopaminergic population of AVPV region of hypothalamus in the male brain.